Animal-Assisted Interventions in Paediatric Hospitals: An Investigation of Italian Healthcare Personnel Attitudes - Cinzia Correale; Sofia Orlando; Marta Borgi; Simonetta Gentile; Simona Cappelletti (Children)
Background: Evidence of the beneficial effects of animal-assisted interventions (AAI) on patients admitted to paediatric hospitals is growing. However, there is still little information about healthcare professionals’ knowledge of and attitudes towards AAI, both as a complement to medical treatments and as a tool for improving the workplace environment. The present study explores the perspectives of Italian paediatric hospital staff after the onset of the COVID-19 pandemic. Methods: An online questionnaire was developed and distributed to paediatric hospital personnel across Italy. The questionnaire addressed topics including AAI’ impact on the hospital environment, their role as a resource for patients and families, their effect on staff well-being, and the perception of the feasibility of AAI implementation in hospitals. Data were analysed descriptively and qualitatively. Results: A total of 44 respondents took part in the survey. Most respondents agreed that AAI could improve hospital environments and serve as a valuable resource for patients and families. However, results were more mixed about the effects of AAI on staff well-being and the feasibility of their implementation. Qualitative analysis identified recurring themes including the positive impact of AAI on emotions/general well-being, improved compliance and treatment outcomes, and reduced stress and distress. Concerns included organisational/logistical challenges, hygiene issues, and potential impact on staff workload. Notably, most participants felt that the COVID-19 pandemic had not affected their perception of AAI safety. Conclusions: Most respondents viewed AAI favourably and supported their implementation as a means of benefiting patients and caregivers. Concerns mainly related to organisational and logistical barriers highlight areas that require further exploration in future research.